2013
DOI: 10.1007/s10278-013-9590-y
|View full text |Cite
|
Sign up to set email alerts
|

Black Box Integration of Computer-Aided Diagnosis into PACS Deserves a Second Chance: Results of a Usability Study Concerning Bone Age Assessment

Abstract: Usability aspects of different integration concepts for picture archiving and communication systems (PACS) and computer-aided diagnosis (CAD) were inquired on the example of BoneXpert, a program determining the skeletal age from a left hand's radiograph. CAD-PACS integration was assessed according to its levels: data, function, presentation, and context integration focusing on usability aspects. A user-based study design was selected. Statements of seven experienced radiologists using two alternative types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…At the same time, it was demonstrated that there is a need to speed up the image processing tasks and avoid system failures while it was suggested that the information quality and user interface of systems be improved by using appropriate analysis and needs assessment of the end users. Last, a usability study on integrating CAD to PACS reported numerous weaknesses that users considered important in the context of the integrative workflow such as efficient handling and fast computation [50].…”
Section: Usability -For Effective and Beneficial Ai In Medical Imagingmentioning
confidence: 99%
“…At the same time, it was demonstrated that there is a need to speed up the image processing tasks and avoid system failures while it was suggested that the information quality and user interface of systems be improved by using appropriate analysis and needs assessment of the end users. Last, a usability study on integrating CAD to PACS reported numerous weaknesses that users considered important in the context of the integrative workflow such as efficient handling and fast computation [50].…”
Section: Usability -For Effective and Beneficial Ai In Medical Imagingmentioning
confidence: 99%
“…However, medical images are blurry and distorted, making them more challenging to process than other image types [2]. Biomedical image analysis and processing have recently become an important research topic because of the difficulty in doing so quickly and precisely [3,4]. Emphysema, tuberculosis, edema, aspiration pneumonia, pneumothorax, lung cancer, and recently COVID-19 are all lung diseases that can cause breathing difficulties or ARDS (acute respiratory distress syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…Other usability studies in radiology do provide more detailed qualitative usability information [10][11][12][13]. However, three of these studies [10,12,13] evaluated systems that do not play a critical role in the radiological workflow and one [11] only performed a heuristic evaluation, which means that no actual users took part in the evaluation. Also, all of these studies were conducted in laboratory settings, so they do not provide information about usability issues encountered in clinical practice.…”
Section: Introductionmentioning
confidence: 99%